The effect of auditors’ digital literacy on reduced audit quality behavior: A chain mediation model and the moderating role of prosocial behavior - Maobao Yang; Lei Guo; Gaofei Ren; Qiuhong Wang; Yi Liu (PLoS ONE, 2026)
Reduced audit quality behavior is prevalent in audit practice and poses a serious threat to overall audit quality. With the increasing adoption of digital auditing, auditors’ digital literacy has become essential not only for adapting to the modern audit environment but also for improving audit quality and curbing inappropriate audit practices. This study examines the effect of auditors’ digital literacy on reduced audit quality behavior by introducing digital self-efficacy and task performance as mediating variables and constructing a chain mediation model, while also exploring the moderating role of prosocial behavior. Empirical analysis based on 480 valid questionnaires revealed that digital literacy negatively influences reduced audit quality behavior. Digital self-efficacy and task performance partially mediate this relationship. Additionally, digital self-efficacy positively enhances task performance, resulting in a chain mediating effect. Prosocial behavior moderates these relationships, significantly affecting the mediating roles of digital self-efficacy and task performance. Accordingly, fostering a digitally enabled audit environment that enhances auditors’ analytical efficiency, judgment accuracy, and procedural compliance requires auditors to effectively leverage digital technologies to mitigate audit quality-threatening behavior.